Atrophic rhinitis and pneumonia occurence in hybrid and undefined breed swines from intensive production system - Braga, Juliana Fortes Vilarinho; Teixeira, Maurício de Paula Ferreira; Lopes, João Batista; Klein Júnior, Manoel Henrique; Silva, Silvana Maria Medeiros de Sousa (Comunicata Scientiae, 2016)
The atrophic rhinitis (AR) and pneumonia are among the most frequently diagnosed respiratory diseases in swine production systems and can lead to significant economic losses. The aim of this study was to determine the occurrence and degree of AR and pneumonia in hybrids and undefined breed swine herds submitted to intensive farming system and check if there is an association between the occurrence of these diseases in the herds. For this, we used 30 swines hybrids (Group I) and 30 undefined breed swines (Group II) from intensive farming system. The index of atrophic rhinitis (IAR) of herds for Groups I and II were, respectively, 1.00 and 0.57. In Group I, 20.8% (5/24) of the pigs presented pneumonia, while none of the animals in Group II exhibited this pathology. There was no correlation between the presence of atrophic rhinitis and pneumonia for the studied animals. These are the first data on the occurrence of these diseases in swines of Piauí State, Brazil. We demonstrated that these pathologies are present in animals from intensive farming systems and that occurrence varied according to racial type, being the hybrid swines the most affected animals by AR and pneumonia.